Pengembangan Basis Data Penjualan, Persediaan dan Logistic Tracking: Studi Kasus PT Abhimata Citra Abadi - Ayuliana, Ayuliana; Putri, Nadya Permata; Pranoto, Araminta; Novembry, Ronald (Bina Nusantara University, 2012)
This study aims at designing a database system processes sales, inventory, and goods tracking in accordance with the needs of PT Citra Abadi Abhimata, as well as building the application program. This system records each process in a flow of goods, ranging from the entry of the principal goods until the goods are sold to end customers plus goods tracking. This study uses the fact finding method carried out by a direct field study at the company concerned, interviews with relevant parties, studying the company?s documentation, and literary study of textbooks. Furthermore, database design uses the three design concepts (conceptual design, logical design and physical design), as well as the interface design to create the application program. The result obtained is a data base system and application that can improve the company?s performance since data is stored on a regular basis so that it can be easily obtained when needed. The existence of this database design, along with related application, makes the company easier to manage data and monitor the process of goods flow and produce better work.